Preoperative and intraoperative predictive factors affecting to the time interval of stoma closure in patients at Dr. Sardjito General Hospital, Yogyakarta in 2018-2023 - Pajar Sigit Nugroho; Adeodatus Yuda Handaya; Anis Fuad (Indonesian Journal of Biomedicine and Clinical Sciences, 2025)
Ostomy procedures, frequently indicated for malignancies, significantly impact patient well-being. In certain instances, stoma closure becomes imperative. Despite the lack of consensus regarding the optimal timeframe for temporary stoma closure, this study aimed to delineate predictors associated with the closure timing, thereby enhancing prognostic precision and augmenting patient care strategies. A cross-sectional study was conducted at Dr. Sardjito General Hospital, Yogyakarta, analyzing medical records of patients who underwent primary stoma creation and subsequent closure between January 2018 and December 2023. Factors, including preoperative, disease-related, and intraoperative variables, were analyzed using SPSS version 26.0. Bivariate and multivariate analyses were performed to identify predictors for stoma closure duration. In the colostomy group, body mass index (BMI), underlying disease, and complications were significantly associated with duration of stoma closure by bivariate analysis (p=0.016; 0.036; 0.040), and BMI and hemoglobin level associated with duration of closure by multivariate analysis (p=0.010; 0.044). Increasing BMI, disease stage, chemotherapy use, complications, and lower hemoglobin level predicted a longer closure duration, while chemotherapy reduced the risk. In the ileostomy group, factors such as underlying disease, cancer stage, chemotherapy status, complications, and type of surgery were associated with duration of closure by bivariate analysis (p=0.010; 0.024; 0.002; 0.013; 0.034), with complications associated with duration of closure by multivariate analysis (p=0.008). In conclusion, BMI, underlying diseases, and complications are associated with stoma closure duration. Understanding these factors can aid in risk stratification and optimizing patient management strategies during stoma closure surgeries.